ANALISIS FARMAKOEKONOMI PERESEPAN ANTIBIOTIKA CEFTRIAXONE DAN CEFTAZIDIME PADA PASIEN BEDAH SESAR DI RUMAH SAKIT PANTI RINI YOGYAKARTA - Maria Wisnu Donowati (Sanata Dharma University, 2013)
Abstract: The raising of cesarean section had leaded the abuse of antibiotic prescribing in orderto minimize the wound or urethra infection that came in the caesarean surgery. Pharmaceuticalcare oriented had push pharmacist to care more about patients drug use to increase quality oflive. The aim of this research is to identify the total hospital service cost and calculate totalantibiotic cost, total drug and prescribtion. The data are collected through medical records andhospital service cost of 145 Panti Rini hospital cesarean section patients in 2003. Normality andhomogenity test are using computer programme, ? 95%. The most patient were 25-30 years old,first gestational fist partum and non aborts, cephalopelvic disproportion indication and havingthird class in hospital services. Ceftazidime in Pharodime and Ceftriaxone in Tricefin are themost cephalosphorin third generation that had been used among other antibiotics. Total hospitalcost that must be paid by the third class cesarean section patients are same, Rp. 820,974 in a day.The average of total drug and medical equipment cost and total antibiotics cost are different.Total drug and medical equipment cost in a day by using Pharodime is cheaper Rp. 33,903 thanTricefin. Total antibiotics cost in a day by using Pharodime is cheaper Rp. 34,663 thanTricefin.Keywords: pharmacoeconomic, antibiotic, prescription.